Psychophysiology of duration estimation in experienced mindfulness meditators and matched controls - Otten, Simone; Schötz, Eva; Wittmann, Marc; Kohls, Niko; Schmidt, Stefan; Meissner, Karin (Frontiers in Psychology, 2015)
Recent research suggests that bodily signals and interoception are strongly related to our sense of time. Mindfulness meditators train to be aware of their body states and therefore could be more accurate at interval timing. In this study, n = 22 experienced mindfulness meditators and n = 22 matched controls performed both, an acoustic and a visual duration reproduction task of 8 s, 14s and 20s intervals, while heart rate and skin conductance were continuously assessed. In addition, participants accomplished a heart-beat perception task and two selective attention tasks. Results revealed no differences between meditators and controls with respect to performance in duration reproduction or attentional capacities. Additionally no group difference in heart beat perception scores was found. Across all subjects, correlational analyses revealed several associations between performance in the duration reproduction tasks and psychophysiological changes, the latter being also related to heart beat perception scores. Furthermore, former findings of linearly increasing cardiac periods and decreasing skin conductance levels during the auditory duration estimation task (Meissner and Wittmann, 2011) could be replicated, and these changes could also be observed during a visual duration reproduction task. In contrast to our earlier findings, the heart-beat perception test was not related with timing performance. Overall, although experienced meditators did not differ from matched controls with respect to duration reproduction and interoceptive awareness, this study adds significantly to the emerging view that time perception is related to autonomic regulation and awareness of body states.